Everyday moral economies : food, politics and scale in Cuba - Wilson, Marisa L. 1979- (RGS-IBG book series, 2014)
"Offering a rare glimpse of rural life in modern-day Cuba, this book examines how ordinary Cubans carve out their own spaces for 'appropriate' acts of consumption, exchange, and production within the contradictory normative and material spaces of everyday economic life. Discusses the conflict between the socialist-welfare ideal of food as an entitlement and the market value of food as a commodity Bridges the fields of human geography and anthropology Approaches food networks and the scale of food systems in a novel way Provides a comprehensive look at Cuba today, with coverage of history, politics, economics, and social and environmental justice Enhanced by vivid photos from the field "--